A Rare Interesting Case of Brunner’s Gland Hyperplasia Causing Gastrointestinal Tract Obstruction.: Life Sciences-Pathology - I, Azeem; Vindhu; Suresh, Natarajan (International Journal of Life Science and Pharma Research, 2022)
Brunner glands are exocrine glands that secrete mucus to protect against acid secretion. Brunner gland hyperplasia is an expansion in size and shape of glands due to excess mucus secretion which occurs in cases where acid is secreted in excess notably duodenal ulcer or gastritis. Usually asymptomatic as Brunner gland hyperplasia appears as small nodular growth noticed during endoscopic examination. Some Brunner gland hyperplasia causes gastric outlet symptoms that are seen in our case study, as we present a rare and interesting case of Brunner gland hyperplasia causing blockage of the gastric outlet (rare symptom). Although endoscopic removal was done in suspicion of malignancy and turned out to be benign Brunner gland hyperplasia which we are discussing in our case as an elaborate discussion. The importance of considering Brunner gland hyperplasia as a differential diagnosis for gastric outlet blockage, as well as the use of endoscopic biopsy for ruling out cancer, are reviewed in depth. There have been many reports in the adult literature of Brunner’s gland hyperplasia causing the bleeding, blockage, or forming intestinal or duodenal folds. Similar cases of Brunner gland hyperplasia impeding stomach outflow are highly uncommon and should be reported.In cases of gastric outlet blockage, Brunner gland hyperplasia should be considered as a distinguishing a particular disease or condition from others that present with similar clinical features, and endoscopic assessment with histopathological microscopy may be a valuable tool in preventing needless surgical intervention. This case report research adds to the necessity of endoscopic biopsy.